Digital Poetry And Cultural Identity: Structural Study of The Poems “Hanyalah Anak Desa” and “Sungguh Terlalu, Sangat Menderita” by Gimin Saputra - Aris Yulantomo; Rian Hidayat; Yulia Nelfita (Fakultas Bahasa Seni dan Budaya, 2025)
This study analyzes the meaning and structure of the poems